Imaging Appearances of Odontogenic Cutaneous Sinus Tract - OBAYASHI, Naofumi; IZUMI, Masahiro; ARIJI, Eiichiro; KATSUMATA, Akitoshi; KOBAYASHI, Kaoru; YOSHIDA, Kazuhito; GOTOH, Masakazu; KURITA, Kenichi; NAITOH, Munetaka; SHIMOZATO, Kazuo; ARIJI, Yoshiko (Shika Hoshasen, 2003)
The present study investigated the imaging features of odontogenic cutaneous sinus tract. CT and MR images of 12 patients with odontogenic cutaneous sinus tract were retrospectively investigated. The sinus tracts originated at mandibular teeth in 10 patients, and in the maxilla in only two patients. In patients with infection of mandibular teeth, the imaging features were classified into three types with reference to the location of the fistula and causal teeth. In 6 patients with Type I appearance, infections originated in the mandibular molar and a fistula was formed on the skin surface of the cheek piercing the platysma muscle between the depressor anguli oris and the masseter muscles on axial images. On coronal images, fistura was observed between the buccinator muscle and the attached portion of the palatysma muscle to the mandible. A patient showing Type II appearance had a periapical lesion of the mandibular canine and a fistula was formed between the mentalis and the depressor anguli oris muscles piercing the depressor labii inferioris muscle. In 3 Type III patients showing findings of extensive osteomyelitis of the mandible, sinus tracts opened near the inferior border of the mandible. The opening site of odontogenic cutaneous sinus tracts were restricted by their casual teeth and surrounding anatomical structures, especially by the masseter, depressor anguli oris, buccinator, mentalis and platysma muscles. CT and MR imaging appeared to be useful to depict these features.